Cost-effectiveness of cell salvage and donor blood transfusion during caesarean section: results from a randomised controlled trial. Issue 2 (9th February 2019) - McLoughlin, Carol; Roberts, Tracy E; Jackson, Louise J; Moore, Philip; Wilson, Matthew; Hooper, Richard; Allard, Shubha; Wrench, Ian; Beresford, Lee; Geoghegan, James; Daniels, Jane; Catling, Sue; et al.
Abstract : Objectives: To evaluate the cost-effectiveness of routine use of cell salvage during caesarean section in mothers at risk of haemorrhage compared with current standard of care. Design: Model-based cost-effectiveness evaluation alongside a multicentre randomised controlled trial. Three main analyses were carried out on the trial data: (1) based on the intention-to-treat principle; (2) based on the per-protocol principle; (3) only participants who underwent an emergency caesarean section. Setting: 26 obstetric units in the UK. Participants: 3028 women at risk of haemorrhage recruited between June 2013 and April 2016. Interventions: Cell salvage (intervention) versus routine care without salvage (control). Primary outcome measures: Cost-effectiveness based on incremental cost per donor blood transfusion avoided. Results: In the intention-to-treat analysis, the mean difference in total costs between cell salvage and standard care was £83. The estimated incremental cost-effectiveness ratio (ICER) was £8110 per donor blood transfusion avoided. For the per-protocol analysis, the mean difference in total costs was £92 and the ICER was £8252. In the emergency caesarean section analysis, the mean difference in total costs was £55 and the ICER was £13 713 per donor blood transfusion avoided. This ICER is driven by the increased probability that these patients would require a higher level of postoperative care and additional surgeries. The results of these analyses were shown to be robust for the majority of deterministic sensitivity analyses. Conclusions: The results of the economic evaluation suggest that while routine cell salvage is a marginally more effective strategy than standard care in avoiding a donor blood transfusion, there is uncertainty in relation to whether it is a less or more costly strategy. The lack of long-term data on the health and quality of life of patients in both arms of the trial means that further research is needed to fully understand the cost implications of both strategies. Trial registration number: ISRCTN66118656 .